2023
DOI: 10.1186/s13148-023-01426-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value and immune correlation of IL18 expression and promoter methylation in renal cell carcinoma

Abstract: Background Renal cell carcinoma (RCC) is not sensitive to immunotherapy and has poor prognosis. DNA methylation regulates gene expression, and its abnormal changes are related to many human diseases. Recently, DNA methylation has been found to participate in immune infiltration in various cancers. However, its pattern in RCC remains poorly understood. Results We found that IL18 was significantly over-expressed in RCC tumor tissues compared to norma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…IL18 was first described as an endotoxin-induced serum factor. As part of the IL1 family, IL18 can stimulate systemic and local inflammation by releasing TNF-α, COX2, and GM-CSF ( Wang X. et al, 2023 ). Emerging research indicated that IL-18 plays a significant regulatory role in immunoregulation across various inflammatory and malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…IL18 was first described as an endotoxin-induced serum factor. As part of the IL1 family, IL18 can stimulate systemic and local inflammation by releasing TNF-α, COX2, and GM-CSF ( Wang X. et al, 2023 ). Emerging research indicated that IL-18 plays a significant regulatory role in immunoregulation across various inflammatory and malignant conditions.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 would have a different effect depending on the cell type, which demonstrated by the facts that human pancreatic tumor tissue expresses high levels of IL-18 [152,153,156,157] and low levels of IL-18BP [156] and these are linked to shorter survival and increased metastasis, whereas high levels of plasmatic IL-18 are associated with a better outcome [152]. Similarly, NLRP3-associated IL-18 is found in high levels in plasma of lymphoma [142] and multiple myeloma patients where IL-18 is a predictor of poor survival in multiple myeloma patients [149,158], esophageal carcinoma [159], renal cell carcinoma [160] and gastric carcinoma [161]. High expression of IL-18 is also associated with increased metastases in hepatocellular and breast carcinomas [162,163].…”
Section: Il-18: a Pro Tumoral Cytokinementioning
confidence: 99%